An investigation of the role of c-Jun N-terminal Kinase (JNK) in inflammation-associated cell deterioration in rat hippocampus - Barry, Claire E. (Trinity College (Dublin, Ireland). Department of Physiology, 2005)
c-Jun N-terminal kinase (JNK) is a milogen-activated protein kinase which is activated in response to various types of stress (e.g. ischemia, heat shock, osmotic stress, UV irradiation, and hypoxia). JNK is strongly implicated in mediating detrimental aspects of inflammatory change across a range of cell types, including that associated with neuroinflammation. However, definitive evidence of JNK involvement is still lacking, therefore the objective of these studies was to assess the role of JNK in inflammatory models in vivo, in particular, its involvement in the impairment of long-term potentiation (LTP) observed under these conditions. By using direct inhibition of the kinase and two agents reputed to have antiinflammatory properties, it was intended that the relevance o f JNK and its associated signalling in mediation of inflammatory change would be determined.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin